Research of Competitive Orientation Among Secondary School Seniour Students: Current Trends and Prospects for Nurturing (Case Study of Tyumen Region) - Gennady F. Shafranov-Kutsev; Lyudmila V. Gulyaeva (National Research Mordova State University, 2017)
Introduction: the priorities of socio-economic development facing our country set new requirements to secondary education; a graduate should not only have a certain amount of knowledge, but also be able to build an effective communication strategy, to be prepared for constant professional self-development, to take the initiative, to interact under conditions of rivalry, in other words, to be competitive. Addressing these issues will contribute to the creation of conditions in which objective requirements of the social system would have found understanding among secondary school students, therefore it is necessary to form competitive thinking. The aim of the study was to consider the factors enabling secondary school students to accept knowledge, values and skills of a competitive person needed for further su stainable development. Materials and Methods: a questionnaire survey of high school students was selected for its reliability and validity in studying competitive skills. The design of the questionnaire was developed by the team of the Sociological Laboratory of the Chair of General and Economic Sociology at Tyumen State University. IBM SPSS Statistics 23 software product was used to process and ana lyse the obtained data. Results: the research provides important insights into the dynamics of the social well-being of secondary school students, defines the main determinants of the formation of skills in competitive environment. The results of this study highlight obstacles to this process as well. Discussion and Conclusions: this paper argues that self-dependent decision-making, critical perception of information, willingness to compete enable to form a competitive personality. The findings from this study have significant potential implications for future educational practice. These research materials are relevant for improving the methods and skills of teaching activities and for development of youth policy. Possible areas for further research in the field of studying the characteristics of competitiveness of high school students can be the study of the influence of residence (comparison of the level of competitiveness of students in urban and rural schools); relations with teachers in the context of the formation of motivation for competitive activities; studying the dynamics of the level of competitiveness (conducting repeated sociological research).